Factors associated with medical comorbid conditions in alcohol use disorders-preliminary findings from a general hospital setting in Bangalore, South India - Priya Sreedaran; Bhuvaneshwari Sethuraman; Johnson Pradeep (Telangana Journal of Psychiatry, 2017)
Background: Alcohol use disorders contribute significantly to global morbidity and mortality. Alcohol use disorders are also associated with presence of comorbid psychiatric as well as medical conditions. There is a need to study the factors associated with presence of comorbid medical conditions as this has important health implications. Methods: A chart review of 57 men with alcohol use disorders in a general hospital setting in Southern India was conducted. Data extracted was analyzed to study association of presence of comorbid medical conditions with the following variables: age of individual, age of onset of use, average amount of alcohol consumed and presence of delirium tremens. Results: Most individuals had comorbid medical conditions. Age of individual had a significant association with presence of comorbid medical conditions in alcohol use disorders. Lifetime history of delirium tremens tended towards a significant association with presence of comorbid medical conditions in Alcohol use disorders. Conclusions: Individuals with longer duration of alcohol use disorders are more likely to be diagnosed with comorbid medical conditions. These findings have implications for management of alcohol use disorders